The new Filipino kitchen stories and recipes from around the globe - Chio-Lauri, Jacqueline (Surrey Books, 2018)
The New Filipino Kitchen collects 30 recipes and stories from expat Filipinos, all of whom have taken their favorite dishes with them, preserving their food memories and, if necessary, tweaking their recipes to work in a new environment or, in the case of some chefs, a more modern context. With contributions from the White House executive chef Cristeta Comerford, Bocuse d’Or Norway winner Christian André Pettersen, 2015 MasterChef New Zealand runner-up Leo Fernandez, five-time Palanca Award winner and poet Francis Macansantos, and the “Food Buddha” Rodelio Aglibot, this is a multifaceted, nuanced introduction to the world of Filipino food and food culture.--Provided by publisher.